The value of short and simple measures to assess outcomes for patients of total hip replacement surgery. Issue 3 (1st September 2000) - Fitzpatrick, Ray; Morris, Richard; Hajat, Shakoor; Reeves, Barnaby; Murray, David W; Hannen, David; Rigge, Marianne; Williams, Olwen; Gregg, Paul
Abstract : Objectives —To evaluate the performance of a patient assessed outcome measure, the Oxford Hip Score, in a national study of primary hip replacement surgery. Design —A survey of patients' health status before undergoing primary hip replacement surgery and three months and one year after surgery. Setting —143 hospitals in three NHS English regions. Patients —7151 patients admitted for primary total hip replacement surgery over a period of 13 months from September 1996. Main measures —For patients, Oxford Hip Score and satisfaction with hip replacement and, for surgeons, American Anesthiologists' Society (ASA) classification of physical status. Results —The response rates to the postal questionnaire at three and 12 months follow up were 85.2% and 80.7%, respectively. Including all three administrations of the questionnaire, all except two items of the Oxford Hip Score were completed by 97% or more respondents and only one item at one administration appeared marginally to reduce the reliability of the score. The effect sizes for changes in the score from baseline to three months was 2.50 and to 12 months was 3.05. Patients rated by surgeons as being healthy preoperatively by the ASA classification were somewhat more likely to return a completed questionnaire at three months (79.4% versus 75.3%) and 12 months (72.4% versus 70.3%) than those rated as having poorer health. Conclusions —Overall there was little evidence of difficulties for patients in completing the Oxford Hip Score or of unreliable data, except in relation to one questionnaire item. The instrument was very responsive to change over time and score changes for the Oxford Hip Score related well to patients' satisfaction with their surgery. The instrument is an appropriate measure in terms of validity, responsiveness, and feasibility for evaluating total hip replacement from the perspective of the patient.